Komposisi Tubuh, Pengetahuan Gizi, dan Daya Tahan Atlet Pencak Silat Lumajang - Tri Findasari; Made Pramono; Awang Firmansyah; Anna Noordia (Mutiara Pendidikan dan Olahraga, 2025)
The performance of pencak silat athletes is influenced by several important factors including physical condition, technique, tactics and psychology. This study aims to determine the body composition, level of nutritional knowledge, and endurance of pencak silat athletes. The type of quantitative research uses a non-experimental observational research design, the participants of this study were 20 Lumajang pencak silat athletes, consisting of 9 male athletes and 11 female athletes. The data in this study were obtained from body composition measurements using the Onemed 825 scan body fat scale, nutritional knowledge level tests from the adoption of the Nutrition for Young and Adult Athlete (NUKYA) questionnaire, and endurance tests using the Beep test. The results of the study showed differences in body composition in male and female athletes in terms of body weight indicators, Fat Free Mass (FFM), Skeletal Muscular Mass (SMM) and Body Mass Index (BMI). The athlete's body composition must be improved in the upper extremity muscle mass of the left and right arms and left and right fitness for female and male athletes and reduce fat mass for female athletes. The level of nutritional knowledge is higher for male athletes with fairly good scores and good endurance levels for both female and male athletes. For coaches, it is recommended to provide weight training programs for athletes with Circuit Training and for athletes to be more active in reading and understanding athlete nutritional knowledge.